Estimation of dose conversion factor of thoron progeny using ICRP 130 human respiratory tract model - Rajeswari P Rout; Rosaline Mishra; Arshad T Khan; B K Sapra (Radiation Protection and Environment, 2023)
Thoron is an emerging field of study due to recent realization of its radiological significance. A code has been developed for determination of dose conversion factor (DCF) of thoron progeny based on the revised International Commission on Radiological Protection 130 human respiratory tract model. Using this code, DCF for an adult male doing light exercise with a breathing rate (BR) of 0.75 m3 h−1 was found to be 35.7 nSv h−1 per Bq m−3 which is very close to the UNSCEAR proposed value. If the BR increased to 1.2 m3 h−1 as considered in case of occupational workers, DCF increases by a factor of 1.5. Along with the BR, DCF was also observed to be largely dependent on the particle size of the thoron progeny.